Effects of acidification and preservatives on microbial growth during storage of orange fleshed sweet potato puree - Musyoka, J.; Abong, G.O.; Mbogo, D.; Fuchs, R.; Low, Jan W.; Heck, S.; Muzhingi, T. (Hindawi Limited, 2018)
Orange Fleshed Sweet Potato (OFSP) puree, a versatile food ingredient, is highly perishable limiting its use in resource constrained environments. It is therefore important to develop shelf-stable puree. A challenge test study was carried out to determine the effect of combinations of chemical preservatives and acidification on microbial growth in stored puree. Puree was prepared and treated as follows: control (A); 0.05% potassium sorbate+0.05% sodium benzoate+1% citric acid (B); 0.1% potassium sorbate+0.1% sodium benzoate+1% citric acid (C); 0.2% potassium sorbate+0.2% sodium benzoate+1% citric acid (D); 1% citric acid (E). Samples were inoculated with Escherichia coli and Staphylococcus aureus at levels of 5.2 x 109 cfu/100g and 1.5 x 109 cfu/100g, respectively, before being evaluated during storage for 10 weeks at prevailing ambient temperature (15-25°C) and refrigeration temperature (4°C). Total aerobic counts, yeasts, and molds were also evaluated. E. coli and S. aureus counts declined significantly (p<0.05) by 4 log cycles in all puree treatments except for control and puree with only citric acid. Total viable count, yeasts, and molds were completely inhibited except for puree with only citric acid. Combination of chemical preservatives and acidification is effective in inhibiting pathogens and spoilage microorganisms in sweet potato puree.